Ein Raum — ein Plan: Vorschlag für eine Reform der Raumnutzungsplanung - Peithmann, Ortwin (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The following proposals to modernize and simplify the German spatial planning system intend to unify the different levels of spatial planning within a modern information system. The continuous convergence of planning contents by scale make it unnecessary to have redundant plans on different levels. The technical means (GIS and Telecommunication) and the changing demands of customers connected to the internet recommend a new concept to achieve planning information. The convergence demands for standardization of terms and planning categories. This leads to clearness and transparency concerning the goals of planning, it raises the benefit from the expenses of coordination, makes plans more up to date, eases the discussion on planning goals for politicians and it helps the public to achieve and understand the plans.The proposal ‘one space — one plan’ deals with the function of spatial planning to regulate land use. The duties of spatial development by the planning authorities are not dealt with. The observations mainly focus on the conditions of spatial planning in Lower-Saxony.
Keywords: planning information system; regional planning; urban land use planning; reform of the spatial planning system; Lower-Saxony